Differential modulation of integrin expression in chondrocytes during expansion for tissue engineering - Gößler, Ulrich; Bugert, Peter; Bieback, Karen; Huber, Kerstin; Fleischer, Lars Ingo; Hörmann, Karl; Riedel, Frank (In vivo, 2005)
Cartilage tissue engineering has an important role to play in the generation of graft material for reconstructive surgery. In cultured chondrocytes, the dedifferentiation of cells seems unavoidable for multiplication. Dedifferentiated cells produce matrix of less quality. Normal cartilage is composed of chondrocytes, which are embedded within an extracellular matrix (ECM). The ECM plays a key role in controlling cellular characteristics and contains the integrins as a large family of heterodimeric cell adhesion receptors involved in cell-cell and cell-matrix interactions. In this study, the characteristic changes of integrin expression and expression of matrix proteins during the course of dedifferentiation of chondrocytes in cell culture for 1, 6 and 21 days, analyzed at the mRNA level by microarray analysis and at the protein level by immunohistochemistry, are described. The components of the fibronectin receptor, integrin β1, α5, in conjunction with the ligand fibronectin, were up-regulated during dedifferentiation. Integrin β3 was expressed in the grey area. The components of the vitronectin-receptor, integrin α2b, αv, as well as integrin β5, were activated on day 21, but neither vitronectin nor osteopontin were expressed by the cells. With ongoing dedifferentiation, activation of the GPIIb/GPIIIa receptor was found. The integrins β2, β4, β6, β8 and α2, α4, α6, α7 and α11 were never expressed. ILK, CD47 and ICAP1, as components of the intracellular signalling cascade of several integrins, were activated with ongoing dedifferentiation. In conclusion, a candidate for signal transmission during dedifferentiation is the fibronectin receptor (integrin α5β1) in conjunction with its ligand fibronectin. Other receptors, e.g. for vitronectin and osteopontin (αVβ3) or laminin (α6β1) or their ligands, do not seem to be involved in signal transmission for dedifferentiation. In addition, the GPIIb/IIIa-receptor seems to assist the process of dedifferentiation. Intracellularly, ILK, ICAP1 and CD47 might assist the transduction of the integrin-dependent signals.